Paris for one [large type] : and other stories - Moyes, Jojo, 1969- (Random House Large Print, 2016)
Nell is twenty-six and has never been to Paris. She has never even been on a weekend away with her boyfriend. Everyone knows she is just not the adventurous type. But, when her boyfriend doesn't turn up for their romantic mini-break, Nell has the chance to prove everyone wrong. Alone in Paris, Nell meets the mysterious moped-riding Fabien and his group of carefree friends. Could this turn out to be the most adventurous weekend of her life?